The Pattern of Neural Elements in the Islets of Normal and Diseased Pancreas and in Isolated Islets - Pour, Parviz M; Saruc, Murat (JOP. Journal of the Pancreas, 2011)
Context The association between islet cells and neural elements, the so-called “neuro-insular complex”, has been known for centuries. Objective We examined the expression of beta-III tubulin, in normal pancreases from organ donors, surgical specimens of chronic pancreatitis, surgical specimens of ductal type carcinoma, isolated and purified islets of a 57-year-old male and the pancreases of adult Syrian golden hamsters by immunohistochemistry using a monoclonal antibody to beta-tubulin. Results In the normal pancreas of humans and hamsters, beta-III tubulin was expressed in alpha- and beta-cells, but not in PP cells, neural fibers and gangliae. Occasionally, intra-and peri-insular neural elements were also found. In chronic pancreatitis and pancreatic cancer samples, the number of beta-cells and the immunoreactivity of the beta-III tubulin antibody in islet cells were decreased in most cases. In cultured human islets, devoid of neural elements, no correlation was found between the expression of beta-III tubulin and islet cell hormones. Conclusion Beta-III tubulin is only expressed in the islets derived from the dorsal pancreas and in neural elements. In chronic pancreatitis and pancreatic cancer swelling of intra- and peri-insular nerves occurs, possibly in response to the loss of beta-cells. The secretion of insulin and the expression of beta-tubulin seem to be regulated by nerves. Image: Multi-labeling of normal pancreatic islets.